Graphene as an Electron Shuttle for Silver Deoxidation: Removing a Key Barrier to Plasmonics and Metamaterials for SERS in the Visible. (19th November 2013) - Losurdo, Maria; Bergmair, Iris; Dastmalchi, Babak; Kim, Tong‐Ho; Giangregroio, Maria M.; Jiao, Wenyuan; Bianco, Giuseppe V.; Brown, April S.; Hingerl, Kurt; Bruno, Giovanni
<x xml:space="preserve">Abstract</x> The role of graphene in enabling deoxidation of silver nanostructures, thereby contributing to enhance plasmonic properties and to improve the temporal stability of graphene/silver hybrids for both general plasmonic and meta‐materials applications, as well as for surface enhanced Raman scattering (SERS) substrates, is demonstrated. The chemical mechanism occurring at the graphene–silver oxide interface is based on the reduction of silver oxide triggered by graphene that acts as a shuttle of electrons and as a kind of catalyst in the deoxidation. A mechanism is formulated, combining elements of electron transfer, role of defects in graphene, and electrochemical potentials of graphene, silver, and oxygen. Therefore, the formulated model represents a step forward from the simple view of graphene as barrier to oxygen diffusion proposed so far in literature. Single layer graphene grown by chemical vapor deposition is transferred onto silver thin films, a periodic silver fishnet structure fabricated by nanoimprint lithography, and onto silver nanoparticle ensembles supporting a localized surface plasmon resonance in the visible range. Through the study of these nanostructured graphene/Ag hybrids, the effectiveness of graphene in preventing and reducing oxidation of silver plasmonic structures, keeping silver in a metallic state over months at air exposure, is demonstrated. The enhanced and stable plasmonic properties of the silver‐fishnet/graphene hybrids are evaluated through their SERS response for detecting benzyl mercaptane.